Carbon supplementation and microbial management to stimulate artemia biomass production in hypersaline culture conditions. (23rd December 2015) - Gao, Meirong; Wang, Jiao; Ma, Guannan; Van Stappen, Gilbert; Sui, Liying
Abstract: Two Artemia culture experiments were conducted in a zero water exchange system at salinity 80 g L −1 . In Experiment I, different carbon sources including molasses, glucose, sucrose and corn flour were given to supplement suboptimal feeding with the microalgae Dunaliella viridis, whereas the control was fed only D. viridis . In Experiment II, molasses was supplemented to the culture medium, as well as the bacteria Alkalibacterium sp. or the archaea Halobacterium sp., isolated from the brine in the local saltponds. The control groups were fed only with D. viridis or with D. viridis and molasses. Our study shows that in laboratory culture biofloc development can be stimulated under hypersaline conditions. Supplementation of carbon sources, bacteria and archaea benefited biofloc development, water quality in terms of nitrogen load and enhanced Artemia production. Denaturing gradient gel electrophoresis analysis on the bioflocs also indicates an increased biodiversity and richness of the microbial community in the culture medium. These results need to be confirmed for large scale Artemia pond production, in which case, we recommend molasses as carbon source.